Interferon-Induced Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Prolonged, refractory status epilepticus in a 22-month old girl treated with interferon for giant cell hepatitis is reported from the Depts of Neurology and Pediatrics, University of Texas Southwestern Medical School, Dallas, TX.